On the role of drawing geometry in the training of technical specialists - Kuzembaev S.B. Кузембаев С.Б.; Alzhanov M.K. Альжанов М.К.; Tuleuova G.K. Тулеуова Г.К. (Рroblems of engineering and professional education, 2022)
In this article, a method is proposed for a comprehensive assessment of the quality of special protective clothing for firefighters, including experimental verification of materials and theoretical studies using a mathematical model.